Dental Manifestations of Ehlers-Danlos Syndromes: A Systematic Review - Ines Kapferer-Seebacher; Dagmar Schnabl; Johannes Zschocke; F. Michael Pope (Medical Journals Sweden, 2020)
Ehlers-Danlos syndromes (EDS) are a group of inherited connective tissue disorders characterized by joint hypermobility, skin hyperextensibility, and variable tissue fragility. However, there are limited published data on the dental manifestations of EDS. This review systematically assessed the spectrum of published dental anomalies in various types of EDS. Twenty-four individual case reports/series and 3 longer case-control studies, reporting on a total of 84 individuals with a clinical diagnosis of EDS, were included in the data analysis. The main dental features listed in classical EDS were pulp calcification and localized root hypoplasia. Common dental abnormalities observed in vascular EDS were pulp shape modifications (52.2%), exceeding root length (34.8%), and molar root fusion (47.8%). Dentinogenesis imperfecta is a consistent finding in osteogenesis imperfecta/EDS overlap syndrome. Data on dental manifestations in other types of EDS are both rare and generally inconclusive.